Adsorption of C14EO8 at the interface between its aqueous solution drop and air saturated by different alkanes vapor - Miller, R; Aksenenko, E V; Kovalchuk, V I; Fainerman, V B (Physical chemistry chemical physics : PCCP, 2017)
The dynamic and equilibrium surface tension for drops of aqueous C14EO8 solutions at the interface to pure air or pentane, hexane, heptane and toluene saturated air, and the dynamic surface tension of pure water at these interfaces are presented. Two theoretical models were employed: both assuming a diffusion controlled adsorption of the surfactant, and either a diffusion or kinetic barrier governed adsorption of the alkanes. The experimental results are best described by the model which implies a diffusion control for the C14EO8 molecules and the existence of a kinetic barrier for the alkane molecules. The desorption of alkanes from the surface layer after equilibration and their subsequent removal from the measuring cell was studied as well. The desorption process was shown to be slow for heptane and hexane. However, for the pentane vapor the desorption is quite rapid, and after the desorption commences the surface tension becomes equal to that at the interface with pure air.The dynamic and equilibrium surface tension for drops of aqueous C14EO8 solutions at the interface to pure air or pentane, hexane, heptane and toluene saturated air, and the dynamic surface tension of pure water at these interfaces are presented. Two theoretical models were employed: both assuming a diffusion controlled adsorption of the surfactant, and either a diffusion or kinetic barrier governed adsorption of the alkanes. The experimental results are best described by the model which implies a diffusion control for the C14EO8 molecules and the existence of a kinetic barrier for the alkane molecules. The desorption of alkanes from the surface layer after equilibration and their subsequent removal from the measuring cell was studied as well. The desorption process was shown to be slow for heptane and hexane. However, for the pentane vapor the desorption is quite rapid, and after the desorption commences the surface tension becomes equal to that at the interface with pure air.